The brothers' Vietnam War : Black power, manhood, and the military experience - Graham, Herman, III, 1967- (University Press of Florida, 2003)
"Clearly focused on exploring the alternative notions of racial manhood which African American servicemen developed during the Black Power era, The Brothers Vietnam War is a welcome addition to the surprisingly small body of scholarly literature on the black experience in Vietnam.